2013
DOI: 10.1016/j.neuint.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Toll-like receptor 2 attenuates Aβ25–35-induced neurotoxicity in organotypic hippocampal slice cultures

Abstract: Toll-like receptors (TLRs), which have been implicated in various neuroinflammatory responses, are thought to act in defense mechanisms by inhibiting neuronal cell death in Alzheimer's disease. In this study, we evaluated the effects of TLR2 on amyloid beta peptide 25-35 (Aβ25-35)-induced neuronal cell death, synaptic dysfunction, and microglial activation in organotypic hippocampal slice cultures (OHSCs) from wild-type (WT) C57BL/6 mice and TLR2-knockout (KO) mice. In WT mice, Aβ25-35 induced β-amyloid aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…This could be a protective mechanism (e.g., shedding or internalization) for decreasing pro-inflammatory cytokine production during overstimulation [ 61 ]. Similar results were obtained for TLR2 expression, except at the basal state of SMC subjects [ 165 , 166 ]. This is in line with data which found that the genomic deletion of TLR2 markedly deteriorated the neurobehavioral functions in a mouse model of AD [ 167 ].…”
Section: Discussionsupporting
confidence: 83%
“…This could be a protective mechanism (e.g., shedding or internalization) for decreasing pro-inflammatory cytokine production during overstimulation [ 61 ]. Similar results were obtained for TLR2 expression, except at the basal state of SMC subjects [ 165 , 166 ]. This is in line with data which found that the genomic deletion of TLR2 markedly deteriorated the neurobehavioral functions in a mouse model of AD [ 167 ].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, synapse elimination is critical in the shaping of neural circuits during development and the regulation of synaptic plasticity in response to experience and memory. Certain neurodegenerative diseases, such as Alzheimer’s disease (AD), are associated with profound synapse loss early in the disease state ( Jana et al ., 2008 ; Meyer-Luehmann et al ., 2008 ; Pihlaja et al ., 2008 ; Suh et al ., 2013 ; Sollvander et al ., 2016 ), which underscores the importance of understanding the molecular mechanisms of synapse loss.…”
Section: Glial Cells Are Involved In Synapse Elimination Via Phagocytmentioning
confidence: 99%
“…Microglia constitutively express TLR2 ( Olson and Miller, 2004 ; Hanke and Kielian, 2011 ), and TLRs play a role in Aβ-induced microglial activation ( Chen et al ., 2006 ; Tahara et al ., 2006 ; Tang et al ., 2007 ; Liu et al ., 2012 ). Aβ-triggered inflammatory activation is reduced in TLR2-deficient microglia ( Jana et al ., 2008 ; Suh et al ., 2013 ), and TLR2 deficiency reduces Aβ-triggered inflammatory activation in cultured microglia, which suggests a beneficial effect of TLR2 inhibition in AD pathogenesis ( Liu et al ., 2012 ).…”
Section: Glial Cell Phagocytosis In Alzheimer’s Disease (Ad)mentioning
confidence: 99%
“…Recent studies demonstrated that activated bone-marrow-derived microglia (BMDM) could uptake Aβ and help to clear Aβ deposition [23], while TLR2 deficit BMDM could not perform its Aβ clearance function; moreover, TLR2 deficiency aggregated cognitive dysfunction in APP/PS1 transgenic mice [24, 25]. In contrast, other studies have reported that long-term administration of the TLR2 inhibitor in AD mice could reduce Aβ aggregation and glial activation [26], and that TLR2 gene knockout and the blocking of the interaction between TLR2 and MyD88 could attenuate the neurotoxicity and pathological changes of AD [27, 28]. While these contradictory phenomena could be interpreted as the consequence of different experimental conditions, such as differences in animal models, observed time points, and cell types, it is nonetheless apparent that TLR2 does play a role in the process of AD, although the exact effect remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%